2003
DOI: 10.1007/s00411-003-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induces a second wave of apoptosis after low dose-rate gamma radiation of HL-60 cells

Abstract: Most cell lines that lack functional p53 protein are arrested in the G(2) phase of the cell cycle due to DNA damage. It was previously found that the human promyelocyte leukemia cells HL-60 (TP53 negative) that had been exposed to ionizing radiation at doses up to 10 Gy were arrested in the G(2) phase for a period of 24 h. The radioresistance of HL-60 cells that were exposed to low dose-rate gamma irradiation of 3.9 mGy/min, which resulted in a pronounced accumulation of the cells in the G(2) phase during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…It was reported by many studies that p53 lacking cells, including HL-60 cells, react to DNAdamaging factors (such as e.g. ionizing radiation or topoisomerase II inhibitors) preferentially by arrest of cell cycle in G2/M phase, which is followed by apoptosis induction (2,15,27,31,32,(36)(37)(38). This was not observed after 2-DG treatment, indicating that direct damage to DNA is not responsible for the antitumor effect of 2-DG.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported by many studies that p53 lacking cells, including HL-60 cells, react to DNAdamaging factors (such as e.g. ionizing radiation or topoisomerase II inhibitors) preferentially by arrest of cell cycle in G2/M phase, which is followed by apoptosis induction (2,15,27,31,32,(36)(37)(38). This was not observed after 2-DG treatment, indicating that direct damage to DNA is not responsible for the antitumor effect of 2-DG.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, caffeine induced a second wave of apoptosis in irradiated HL-60 cells. 20 Jha et al 10 observed that the G2-phase delays were eliminated by caffeine in the tumor cell lines (HeLa, MCF7, OVGI), but in sharp contrast, caffeine did not eliminate or even reduce the gamma-ray-induced G2-phase delays in any of the human normal cell lines (GM2149, GM4626, AG1522). This was important for the radiosensitization effect of caffeine in clinical application because caffeine can enhance the radiosensitivity of the hepatocellular carcinoma cell and cannot cause the additional burden on the normal liver cell at the same time.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, D0-values obtained from the multi-target formalism fall within the range of those reported in in vitro and in vivo studies using cells originating from a wide variety of malignancies. 1,[28][29][30][31][32][33][34][35] Although there were changes in rank-order between D0-values obtained from the multi-target and linear-quadratic (LQ) formalisms, they did not significantly affect the variations of D0 within each group of cell lines ( Table 1). Specifically, the coefficients of variation in D0…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of highly radiosensitive ataxia telangiectasia cells, typical D0-values for tumor and normal cells have been found to range between~0.9 and 3.7 Gy. 1,[28][29][30][31][32][33][34][35] To test the strength of our model for extrapolating radiosensitivity at doses for which in vitro experimental data cannot be generated, the data presented in larly derived from  and  parameters that were reported for glioblastoma, neuroblastoma, and prostate cell lines in other historic studies. [41][42][43][44] The comparison is shown in Figure 5 and illustrates that the current and historical data are congruent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation